Frequent occurrence of nicotinic acetylcholine receptors in GABAergic neurons of the chick visual system - A.S. Torrão; L.R.G. Britto (Brazilian Journal of Medical and Biological Research, 2001)
Double-labeling immunohistochemical methods were used to investigate the occurrence of the alpha8 and alpha5 nicotinic receptor subunits in presumptive GABAergic neurons of the chick nervous system. Nicotinic receptor immunoreactivity was often found in cells exhibiting GABA-like immunoreactivity, especially in the visual system. The alpha8 subunit appeared to be present in presumptive GABAergic cells of the ventral lateral geniculate nucleus, nucleus of the basal optic root of the accessory optic system, and the optic tectum, among several other structures. The alpha5 subunit was also found in GABA-positive neurons, as observed in the lentiform nucleus of the mesencephalon and other pretectal nuclei. The numbers of alpha8- and alpha5-positive neurons that were also GABA-positive represented high percentages of the total number of neurons containing nicotinic receptor labeling in several brain areas, which indicates that most of the alpha8 and alpha5 nicotinic receptor subunits are present in GABAergic cells. Taken together with data from other studies, our results indicate an important role of the nicotinic acetylcholine receptors in the functional organization of GABAergic circuits in the visual system.